2,100 years of human adaptation to climate change in the High Andes - Åkesson, Christine M. (2020)
Humid montane forests are challenging environments for human habitation. We used high-resolution fossil pollen, charcoal, diatom and sediment chemistry data from the iconic archaeological setting of Laguna de los Condores, Peru to reconstruct changing land uses and climates in a forested Andean valley. Forest clearance and maize cultivation were initiated during periods of drought, with periods of forest recovery occurring during wetter conditions. Between ad 800 and 1000 forest regrowth was evident, but this trend was reversed between ad 1000 and 1200 as drier conditions coincided with renewed land clearance, the establishment of a permanent village and the use of cliffs overlooking the lake as a burial site. By ad 1230 forests had regrown in the valley and maize cultivation was greatly reduced. An elevational transect investigating regional patterns showed a parallel, but earlier, history of reduced maize cultivation and forest regeneration at mid-elevation. However, a lowland site showed continuous maize agriculture until European conquest but very little subsequent change in forest cover. Divergent, climate-sensitive landscape histories do not support categorical assessments that forest regrowth and peak carbon sequestration coincided with European arrival.